2007
DOI: 10.1080/15578770701715003
|View full text |Cite
|
Sign up to set email alerts
|

Capital Equipment Acquisition in Heavy Construction

Abstract: Capital equipment acquisition is an important process in the heavy construction industry. Equipment is often one of the largest investments for a company and has a significant effect on cash flow and profit potential. The purpose of this article is to investigate capital equipment acquisition processes of heavy construction companies. The equipment acquisition process was analyzed by evaluating equipment replacement policies, the position of the individual making equipment purchasing decisions, and the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The aim is to decide which solution is better tailored to a firm's desires and financial framework, and the SME entrepreneur identifies the right options and assess funding decision-making [7,9,22]. The purchasing and upkeep of equipment can constitute a huge part of the assets of an organization and can affect income [65]. Hence, the performance of the business is a component of project progress, and equipment acquisition has an effect on the cash flow and profitability of the organization owing to the high costs of ownership.…”
Section: Entrepreneur Motivation and Sources Of Financingmentioning
confidence: 99%
“…The aim is to decide which solution is better tailored to a firm's desires and financial framework, and the SME entrepreneur identifies the right options and assess funding decision-making [7,9,22]. The purchasing and upkeep of equipment can constitute a huge part of the assets of an organization and can affect income [65]. Hence, the performance of the business is a component of project progress, and equipment acquisition has an effect on the cash flow and profitability of the organization owing to the high costs of ownership.…”
Section: Entrepreneur Motivation and Sources Of Financingmentioning
confidence: 99%
“…They can be bought or rented, and they are expensive in terms of cost to an extent that; they can impact cash flow and profit potential of a SMSBC company due to the high costs associated with ownership, i.e. acquisition, principle and interest, taxes, maintenance, and replacement, Clapp et al (2007). According to Vorester (2005) in Clapp et al (2007), heavy building construction equipment costs average approximately 30% of the company assets, thus underlining capital equipment as often one of the largest investments for a SMSBC company.…”
Section: Non-payment Of Debts and Price Fluctuation;mentioning
confidence: 99%
“…acquisition, principle and interest, taxes, maintenance, and replacement, Clapp et al (2007). According to Vorester (2005) in Clapp et al (2007), heavy building construction equipment costs average approximately 30% of the company assets, thus underlining capital equipment as often one of the largest investments for a SMSBC company. Clapp et al (2007) insists on building construction companies to have an equipment acquisition policy, as it has a great impact on the profitability of any building construction firm.…”
Section: Non-payment Of Debts and Price Fluctuation;mentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is consistent with Dulaimi and Hong (2002), who found that about 30 per cent of their respondents leased 50-70 per cent of their construction equipment. Clearly, buying construction machinery and equipment is one of the largest investments that could have significant effect on a company's cash flow, and thus greater emphasis should be given to comparing the cost-effectiveness between leasing and purchasing of machinery and equipment (Punwani, 1997;Clapp et al, 2007). It is noted that the rest of the companies interviewed had either leased all machinery and equipment required (24 per cent of firms), or purchased various machinery and equipment and established subsidiaries involving the leasing of construction machinery (8 per cent of the firms).…”
Section: Strategies Of Singapore Contractorsmentioning
confidence: 99%